Analisis Praktek Hibah Pengganti Warisan di Kalangan Umat Islam Indonesia - Sukiati; Muhammad Hidayat; Muhamad Hasan Sebyar (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to explore the patterns of Hibah practice as a substitute for inheritance in Indonesian society and the reasons they do so. The research locations include Gayo, Aceh, North Sumatra, Jambi, Madiun, Kediri and Surabaya. In this qualitative study, data were collected through interviews. The participants consisted of ulama, academics, and the community who practice Hibah as a substitute for inheritance. Interviews were transcribed and analyzed through content analysis. This study indicates three patterns of Hibah practice as a substitute for inheritance. First, the Hibah is given at the beginning with a portion of 2:1, which is also considered an inheritance when the parent dies. Second, the Hibah is divided equally as well as the surviving parent gets a share. When someone dies, the assets owned by the parents are divided equally. Third, the Hibah is divided unequally, and after the parent dies, the property becomes a portion of the inheritance calculation. This study concludes that the practice of Hibah is becoming more popular among the people in distributing the inheritance, while Islamic inheritance is increasingly insignificant. The position of religious law which is so important in Indonesian Muslim society is critical.